1994
DOI: 10.1293/tox.7.73
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological findings of the urinary bladder epithelium in aged dogs.

Abstract: Abstract:Apparently normal urinary bladder of beagle dogs of both sexes were examined histopath

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…These previous studies indicated that dog bladder tumor shows patterns of histogenesis and progression similar to the natural history of human bladder cancer, and that it is highly useful as a model of human bladder cancer. As described in our previous report [16], our histopathological examination of changes in the bladder epithelium of 50 elderly beagle dogs suggested the high utility of beagles for experiments involving bladder carcinogenesis. The present study was undertaken to study histopathologically two types of bladder tumor induced in mongrel dogs.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These previous studies indicated that dog bladder tumor shows patterns of histogenesis and progression similar to the natural history of human bladder cancer, and that it is highly useful as a model of human bladder cancer. As described in our previous report [16], our histopathological examination of changes in the bladder epithelium of 50 elderly beagle dogs suggested the high utility of beagles for experiments involving bladder carcinogenesis. The present study was undertaken to study histopathologically two types of bladder tumor induced in mongrel dogs.…”
Section: Discussionsupporting
confidence: 67%
“…When the urinary bladder mucosa of elderly beagles was examined, the lamina propria of every region of the mucosa in all dogs had Brunn's nests, and the same finding was obtained in 66.7% of younger beagles [16]. Brunn's nests are regarded as representing proliferative changes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Papillary shaped-bladder tumors have been known to be more indolent than nodular-shaped ones. This concept is supported by animal model investigations regarding urothelial carcinogenesis [ 23 24 25 26 27 28 29 30 31 ].…”
Section: Favorable Prognosis Of Papillary Bladder Tumors Verified In mentioning
confidence: 81%
“…BBN-induced urothelial carcinogenesis of the bladder in dogs (beagle dogs and mongrel dogs) has been investigated in detail by our colleagues, Okajima et al [ 26 27 28 29 30 ]. When 2 beagles were treated daily with 160 mg of BBN in oral capsules, multifocal papillary G1/G2 tumors were seen 137 weeks after the initiation of BBN treatment.…”
Section: Favorable Prognosis Of Papillary Bladder Tumors Verified In mentioning
confidence: 99%